The role of psychological hardness in improving the skill performance of football players Afield study on the coaches of the wilayat of Awlad jalal - طنش, محمد; حريزي, عبد الهادي (sports creativity, 2025)
The study aims to know the role and importance of psychological toughness in improving the skill performance of football players, and knowing the level of psychological toughness of the football player and its evaluation through the performance of the players during the performance of skills, whether offensive or defensive, as it is one of the important pillars for the coach and player during the training process, where it represented The problem of the study in what is the role of psychological hardness on the skill performance of football players? As for the methodology of the study, we used the descriptive approach using the questionnaire tool and chose an intended sample consisting of 28 coaches in the Wilayat of Awlad Jalal, then we distributed the questionnaire to them, and through the results obtained, we concluded that psychological toughness has an effective and